Early to recognize and Early to recover: A case series on Thyrotoxic periodic paralysis (Indian Journal of Case Reports, 2022)
Thyrotoxic periodic paralysis (TPP) is a rare disease of muscle, presenting with sudden onset weakness of muscles with or without features of hyperthyroidism. The disease most commonly occurs in the Asian population representing about 1.9% of thyrotoxic patients. It involves a predominantly male population with no family history, with or without hypokalemia. Pathophysiology is still not clearly understood. We are describing, a case series of two different patients of TPP presented to our emergency department (ED). One patient presented with classical episodic weakness of both lower limbs specifically during the night times with spontaneous reversal of weakness early in the morning. Another patient presented with complete weakness of both lower limbs for the past 1 day. Both of them had a history of weight loss and intermittent palpitations. They were promptly diagnosed in the ED and successfully treated. We recommend evaluating thyroid function status in the emergency room with the aforementioned clinical features, as early recognition and correction of thyrotoxic state are the definitive treatment helping in a complete reversal of weakness. Potassium supplements, beta-blockers, and antithyroid medications are used in treating acute attacks and preventing recurrence.